Teachers Role to Cultivate Tolerance among Students at Graduate Level: https://doi.org/10.55966/assaj.2025.4.1.078 - Ayesha Saddiqa; Dr. Rashid Minas Wattoo (`, 2025)
Teachers play a decisive role in fostering tolerance through inclusive classroom environments, encourage critical thinking, and model respectful dialogue. In order to assess the role of teachers to cultivate tolerance among college students’ researcher used explanatory sequential mixed-method research design. Population for this study was all Government Graduate Colleges (Women) and working teachers in Government Graduate Colleges (Women) from District Sialkot. Stratified random sampling technique was used to select sample from different departments of BS level program. Sample size was 204 students and 50 teachers from Tehsil Sambrial and Sialkot of District Sialkot. Data was gathered through two questionnaires, one is self-developed questionnaire which collected data from students and other questionnaire comprises an open ended question which collects data from teachers. Frequency, percentage, mean score, standard deviation, and T.test were used to analyses of data. Thematic analysis was also used to analysed the open ended question. The result of the study depicts that a potential area for improvement because the outcomes of study recommended that educators may not find success in encouraging pupils to interact each other with respect and avoid biases. The study highlights the need of opportunities to promote tolerance effectively. A critical number of respondents accept that educators didn’t organize collaborative activities, cultural exchange projects, or conversations about cultural diversity and decrease prejudices. Keywords: Cultivate Tolerance, Critical Thinking, Social Harmony, Democratic Engagement